2005
DOI: 10.1002/ijc.21004
|View full text |Cite
|
Sign up to set email alerts
|

High‐throughput protein expression analysis using tissue microarray technology of a large well‐characterised series identifies biologically distinct classes of breast cancer confirming recent cDNA expression analyses

Abstract: Recent studies on gene molecular profiling using cDNA microarray in a relatively small series of breast cancer have identified biologically distinct groups with apparent clinical and prognostic relevance. The validation of such new taxonomies should be confirmed on larger series of cases prior to acceptance in clinical practice. The development of tissue microarray (TMA) technology provides methodology for high-throughput concomitant analyses of multiple proteins on large numbers of archival tumour samples. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

20
513
0
6

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 505 publications
(539 citation statements)
references
References 46 publications
20
513
0
6
Order By: Relevance
“…This study was based on a well-characterised cohort of early stage (I-III) primary operable invasive BC (n=1902) from patients enrolled into the Nottingham Tenovus Primary Breast Carcinoma Series between 1987 and 1998, and managed in accordance to a uniform protocol and has been comprehensively studied with a broad range of markers [9,10]. During the follow-up time within this series, distant recurrence had developed in 578/1902 cases (30 %).…”
Section: Patients and Tumoursmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was based on a well-characterised cohort of early stage (I-III) primary operable invasive BC (n=1902) from patients enrolled into the Nottingham Tenovus Primary Breast Carcinoma Series between 1987 and 1998, and managed in accordance to a uniform protocol and has been comprehensively studied with a broad range of markers [9,10]. During the follow-up time within this series, distant recurrence had developed in 578/1902 cases (30 %).…”
Section: Patients and Tumoursmentioning
confidence: 99%
“…This study included 31 biomarkers of clinical and biological relevance to BC tumourigenesis and progression [9,11] Primary Breast Carcinoma series previously studied using gene expression profiling [14].…”
Section: Patients and Tumoursmentioning
confidence: 99%
“…Despite the fact that varying criteria have been used to define each category, many studies have shown immunohistochemicalbased classifiers to be prognostically significant. [5][6][7] Luminal A cancers have been defined by a number of groups as hormone receptor-positive and HER2-negative and luminal B cancers as both hormone receptor positive and HER2 positive. [8][9][10][11][12] However, this definition is flawed as B70% of luminal B tumors, defined by gene expression profiling, are in fact HER2 negative.…”
mentioning
confidence: 99%
“…This variety of breast carcinoma was characterized by genetic studies and by immunohistochemical expression of basal cytokeratins, mainly types 5, 14 and 17, epidermal growth factor receptor (EGFR) and p53, [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] but results from diverse studies are not always concordant. Recently, 'pure' and 'myoepithelial' variants of basal breast carcinoma were described, based on S-100, actin or p63 expression.…”
mentioning
confidence: 99%